Eu-doped Si-SiO2 core–shell nanowires for Si-compatible red emission. (25th August 2016) - Xu, Jinyou; Guo, Pengfei; Zou, Zhijun; Lu, Yang; Yan, Hailong; Luo, Yongsong
Abstract: The indirect bandgap of single-crystalline silicon has so far precluded the full integration of silicon microelectronics with photonics—which is expected to allow the realization of low-cost, high-speed optical information processing and communication in the future. Here we report the growth of europium (Eu)-doped Si-SiO2 core–shell nanowires by an oxide-assisted chemical vapor deposition method. The Eu concentration in these nanowires is effectively improved by intentionally increasing the thickness of SiO2 shells. As a result, a strong Si-compatible red emission from Eu 3+ ions was observed under laser illumination. The effect of Eu 3+ concentration on the emission efficiency was comprehensively studied, with the highest efficiency at Eu content about 0.8 at%. The relaxation mechanism of this concentration dependent luminescence was further explored through lifetime measurements. In light of the strong characteristic red emission and nanoscale footprint, these nanowires are promising Si-compatible light emission materials for future integrated nanophotonics.